ZnO nanoplates surfaced-decorated by WO3 nanorods for NH3 gas sensing application. (27th January 2016) - Nguyen, Dac Dien; Do, Duc Tho; Vu, Xuan Hien; Dang, Duc Vuong; Nguyen, Duc Chien
Abstract: Zinc oxide (ZnO) nanoplates and tungsten trioxide (WO3 ) nanorods were synthesized by hydrothermal treatment from zinc nitrate/potassium hydroxide and sodium tungstate/hydrochloric acid, respectively. The structure, morphology and compositions of the as-prepared WO3 /ZnO nano-composites were characterized by x-ray diffraction, field emission scanning electron microscopy and energy dispersive spectroscopy. The obtained ZnO nanoplates have regular shape, single-crystal wurtzite structure with the thickness of 40 nm and 200 versus 400 nm in lateral dimensions. The WO3 nanorods possess the average diameter of 20 nm and the length of approximately 120 nm which were distributed on the surfaces of ZnO nanoplates. The WO3 /ZnO nano-composites were prepared by grinding WO3 nanorods powder with ZnO nanoplates powder in various weight ratios (1:2, 1:1 and 2:1). The NH3 gas sensing properties of WO3 /ZnO nano-composites were examined through the electrical resistance measurement. The gas sensing performance of the WO3 /ZnO composite with weight ratio of 1:1 was better compared with that of other samples. For this sample, the maximum response to 300 ppm NH3 was 24 at the operating temperature of 250 °C. In addition, the gas sensing mechanism of the WO3 /ZnO composites was discussed.